913Factors of premature atrial contractions among general Japanese men. (2nd September 2021) - Ahmed, Sabrina; Miura, Katsuyuki; Hisamatsu, Takashi; Kadota, Aya; Fujiyoshi, Akira; Segawa, Hiroyoshi; Torii, Sayuki; Takashima, Naoyuki; Kondo, Keiko; Ueshima, Hirotsugu
Abstract: Background: Premature atrial contractions (PACs) are known predictor of atrial fibrillation; however very little has been revealed on its factors among Asian general population. We assessed the frequency of higher PAC counts and its association with relevant factors in general Japanese men. Methods: We have conducted a population based cross sectional study among 517 healthy men from Kusatsu, Japan, aged between 40 and 79 years. 24 hours Holter electrocardiogram was performed to assess the PAC frequency. We divided participants into quartiles based on number of PACs/hour to compare the characteristics by using Cochran–Mantel–Hanzal test and ANOVA. We defined the highest quartile as event and multivariable logistic regression was performed to assess the significance with relevant factors. Results: Median number of PACs was 2.84 PACs/hour. The highest quartile of PAC counts was >7.86PACs/hour. Age, triglycerides, blood pressure, ventricular contractions and heart rates were different among quartiles. In multivariable logistic regression analysis, higher age (OR, 95% CI: 1.35, 1.01-1.67), lower mean heart rates (OR, 95% CI: 0.97, 0.94-0.99), higher heart rate difference in a day (OR, 95% CI: 1.40, 1.12-1.75) and lower triglyceride (OR, 95% CI: 0.53, 0.33-0.82) were independently, significantly associated with highest quartile of PACs. Conclusions: Higher PACs evaluated by Holter ECG was associated with higher age, lower heart rate, higher heart rate difference, and lower triglyceride in general Japanese men. Key messages: The PAC frequency was high. Age, mean heart rates, difference between maximum and resting heart rates, triglycerides are possible risk factors for frequent PAC counts.